Impact of Mosquito Gut Microbiota on Propagating Pathogenic Infections - Bhowmik, Biplab; Saha, Swadhin Kumar; Pramanik, Monalisa; Mondal, Swarupa; Roy, Priya (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The mosquito vectors of various human diseases host a diversified microbial community. These microbiomes seem to be beneficial in several aspects of mosquito biology. They can influence mosquitoes’ susceptibility to various pathogenic infections, therefore affecting the vectorial capacity of mosquitoes through different direct or indirect mechanisms. These microbes act as natural barriers against several mosquito-transmitted infectious diseases. They may be considered as a new transmission-blocking strategy to limit the transmission of pathogens like Plasmodium, Trypanosome, Zika, Dengue and Chikungunya viruses, and filarial parasites. It is through an understanding of the interaction between the mosquito, its microbiota, and the transmitted pathogens that some promising approaches may be developed for limiting the transmission of pathogenic diseases.In this review, we investigate the role of mosquito’s gut microbiome in the propagation of pathogenic infections. It is summarized here in a brief manner how the current knowledge is used for the purpose of limiting the transmission of mosquito-borne diseases through the alteration of mosquitoes' vector capacities.